1
$\begingroup$

I've used Parseval's theorem before, to calculate $\sum_{n=1}^\infty \frac{1}{n^4}$. Now I have to calculate $ \sum_{n=1}^\infty \frac{1}{(2n-1)^4}$ and I'm lost. I have to start with $f(x)=x, x\in[0,\pi]$. My Fourier coefficients are: $$a_0=\frac{\pi}{2}$$ $$a_n=\frac{(-1)^n-1}{\pi n^2}$$ $$b_n=\frac{(-1)^{n+1}}{n}$$ I've also managed to calculate $\sum_{n=1}^\infty \frac{1}{(2n-1)^2}=\frac{\pi ^2}{8}$. I've tried to do it: calculating $|a_0|^2$ is easy, but I have problem with $\sum_{n=1}^\infty |a_n|^2+|b_n|^2$, I get $\frac{-2}{\pi} \sum_{n=1}^\infty \frac{(-1)^n -1 -\pi}{n^2}$, which leads me nowhere. Am I doing something wrong? Or is it correct? In both cases, I think I need just a little help with this.

$\endgroup$
1
$\begingroup$

By comparing even numbers to odd numbers, we find that

\begin{align} \sum_{n \in \mathbb{N}} \frac 1 {n^4} &= \sum_{n \text{ even}} \frac 1 {n^4} + \sum_{n \text{ odd}} \frac 1 {n^4} \\ &= \frac 1 {2^4} \sum_{k \in \mathbb{N}} \frac 1 {k^4} + \sum_{k \in \mathbb{N}} \frac{1}{(2k - 1)^4} \end{align}

so that

$$\sum_{k \in \mathbb{N}} \frac 1 {(2k - 1)^4} = \frac {15}{16} \cdot \frac{\pi^4}{90} = \frac {\pi^4}{96}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.